1977
DOI: 10.1111/j.1365-246x.1977.tb04198.x
|View full text |Cite
|
Sign up to set email alerts
|

Secular trend of the Earth's rotation pole: Consideration of motion of the latitude observatories

Abstract: Secular polar motion has been recorded in ILS data over the past 75 years, an amount greater by a factor of ten than the 'true polar wandering' deduced from paleomagnetic data. In this work, the possibility that the secular trend is an observational artifact of the continental drift of the ILS stations is directly examined by consideration of several absolute plate velocity models earlier proposed by Minster et al.(1 974), Kaula (1 9 7 9 , and Solomon, Sleep & Richardson (1975). The assumptions underlying thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…and the Earth's rotation generally assumed' that the observed signals [e.g., Curroll 1966; Dickman, 1977] were due exclusively to the rebound process, and the primary aim of these studies was to infer the radial pro- In the last few years, attempts to constrain the signal from ongoing melting events has continued to be 985 an active area of study. Trupin et al [1992].have considered, in detail, the contribution to both J2 and polar wander from the mass balance of sinall ice sheets and glaciers over the period [1965][1966][1967][1968][1969][1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984].…”
Section: Introductionmentioning
confidence: 99%
“…and the Earth's rotation generally assumed' that the observed signals [e.g., Curroll 1966; Dickman, 1977] were due exclusively to the rebound process, and the primary aim of these studies was to infer the radial pro- In the last few years, attempts to constrain the signal from ongoing melting events has continued to be 985 an active area of study. Trupin et al [1992].have considered, in detail, the contribution to both J2 and polar wander from the mass balance of sinall ice sheets and glaciers over the period [1965][1966][1967][1968][1969][1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984].…”
Section: Introductionmentioning
confidence: 99%
“…The unambiguous connection between this polar wander and the GIA process was first established by Peltier [1982] and Wu and Peltier [1984], whose detailed theoretical analysis, since further generalized by Peltier and Jiang [1996a], showed that the initial analysis of the GIA effect provided by Munk and MacDonaM [1960] did not, in fact, rule out a significant ongoing wander due to this cause, as they had imagined, even though the surface mass load during the present interglacial period is very nearly time invariant. The analysis of the data by Dickman [1977] has now also been performed by many others, and their results are all compiled on Figure 12b. Also shown on Figure 12b is the result of an additional measurement based upon VLBI data by Carter et al [1986].…”
Section: Astronomical Signatures Of the Ice Age Cyclementioning
confidence: 99%
“…What is of greatest interest from the sea level perspective, however, as we shall see, is the slow secular drift of the pole upon which these oscillatory variations are superimposed. According to Dickman [1977] this "truepolar wander" is occurring at a rate near 0.95 ø per million years along the 76øW meridian as shown on the inset polar projection. The unambiguous connection between this polar wander and the GIA process was first established by Peltier [1982] and Wu and Peltier [1984], whose detailed theoretical analysis, since further generalized by Peltier and Jiang [1996a], showed that the initial analysis of the GIA effect provided by Munk and MacDonaM [1960] did not, in fact, rule out a significant ongoing wander due to this cause, as they had imagined, even though the surface mass load during the present interglacial period is very nearly time invariant.…”
Section: Astronomical Signatures Of the Ice Age Cyclementioning
confidence: 99%
“…This limits the concept of TPW to periods of about 100 Myr, and one should be careful not to misinterpret a redistribution of hot spots during plate reorganization periods as a "catastrophic turnover" of the rotation axis. Apart from this, there is evidence of TPW on both timescales of millions of years [Besse and Courtillot, 1991] and thousands of years [Dickman, 1977] Other uncertainties that accompany deriving radial viscosity profiles from rotational studies are the neglect of lateral viscosity variations and uncertainties in the load history of the Pleistocene ice models. There are reasons, however, that these will affect the results to a lesser extent.…”
mentioning
confidence: 99%
“…The observational data considered in our analysis are taken from Dickman [1977] and McCarthy and Luzum hot spots is still a matter of debate, one could associate them with more or less stationary mantle convection patterns. This would imply that whenever a large change of the global convection pattern emerges, being accompanied by a large reorganization of the plates, then the concept of true polar wander becomes meaningless as the hot spot reference frame is destroyed or reorganized.…”
mentioning
confidence: 99%